THE RESULTS OF APPLYING STEM EDUCATION TO ENHANCE UNDERSTANDING OF LEARNING MANAGEMENT BASED ON THE STEM EDUCATION FOR THE STUDENTS IN THE FACULTY OF EDUCATION, UTTARADIT RAJABHAT UNIVERSITY - Ounraun, Walida (PEOPLE: International Journal of Social Sciences, 2019)
The objectives of this research were to 1) enhance knowledge and understanding of learning management based on STEM Education guidelines before and after learning 2) to study the satisfaction of the students towards this learning management. The data of this research were 30 students in Physics Department, Faculty of Education at Uttaradit Rajabhat University in the 2nd semester in 2017. The samples were chosen by a purposive sampling. The research instruments included a test examining student’s knowledge and understanding of this learning management and the form evaluating students’ satisfaction. The data were analyzed using mean, and the standard deviation, and t-test dependent. The results revealed that 1) the achievements on the students’ knowledge and understanding of learning management based on STEM Education guidelines after learning were higher than those of before with statistical significance at .05 level and 2) the students’ satisfaction was at a high level (x = 4.17).